2022
DOI: 10.4236/jhrss.2022.103021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supportive Organizational Climate on Employee Turnover Intention: A Cross-Level Analysis

Abstract: Employee turnover affects the stable development of enterprise. It is not only an urgent problem that leaders need to think about, but also a research topic that management scholars and economists focus on. Turnover intention can well predict the turnover behavior of employee. Therefore, this paper investigates 50 enterprises and 305 employees in China and uses a cross-level regression model to test the mechanism between supportive organizational climate and employee turnover intention based on the organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…The better the level of organizational climate a company has, the lower the turnover rate in a company will be. In line with this, research conducted by Hao & Wang (2022) found that based on regression results, a supportive organizational climate had a significant negative effect on employee turnover intentions. It also shows that when companies create a supportive type of organizational climate for employees, this can significantly reduce the idea of employees wanting to leave the company.…”
Section: Introductionsupporting
confidence: 52%
“…The better the level of organizational climate a company has, the lower the turnover rate in a company will be. In line with this, research conducted by Hao & Wang (2022) found that based on regression results, a supportive organizational climate had a significant negative effect on employee turnover intentions. It also shows that when companies create a supportive type of organizational climate for employees, this can significantly reduce the idea of employees wanting to leave the company.…”
Section: Introductionsupporting
confidence: 52%